Genetic didactic sequence using Digital Information of Comunication Technologies (DICT) for scientific literacy (Research, Society and Development, 2020)
The present research aims developing and validating a Didactic Sequence, using digital information and communication technologies towards formation of high school students, considering the Scientific Literacy and the deepening of concepts that are present in students' daily life. In addition, the proposal presents itself as a practical possibility of bringing up technologies, scientific knowledge, and making teachers and students closer. It is intended that this Didactic Sequence can be applied as a pedagogical support for the teaching of basic genetics, helping teachers and students in the process of teaching this content. Toward the development of this Didactic Sequence, the Learning Styles and the Scientific Literacy indicators proposed by Sasseron (2008) were considered, aiming the improvement of the students in the Scientific Literacy perspective. The proposed Didactic Sequence was evaluated by three biology teachers who teach both in public and private schools. Evaluators were given a questionnaire containing questions that focused on the structure of the Didactic Sequence in terms of content, organization, form and feasibility of classroom application. The evaluation of the Didactic Sequence, by teachers of the area, proved to be an important instrument for its validation, before its possible application to the students. The obtained results indicate that the resources used for the elaboration of the Didactic Sequence are simple and easy to use, indicating that it can contribute to the teaching and learning of Genetics.